Corporate social responsibility and the entrepreneur through the lenses of the management theories - Mones, Reynaldo A. (Animo Repository, 2011)
Corporate social responsibility in the country has gone through a series of transformations from a simple donation and individual philanthropic activity to a full-blown corporate advocacy ranging from tree planting to education to solid waste management, among others. These projects have involved thousands of manpower that include the employees and management of these corporations and the members of the community where these projects were implemented. These people have sacrificed time away from work and family just to be able to serve. Entrepreneurs are even at the forefront of such activities, oftentimes, participating in the project with their constituents like building homes and cleaning coastal areas. It is this aspect of CSR that led the author to research into the reasons why entrepreneurs engage in CSR activities and analyze and evaluate them relative to the agency theory, the stewardship theory, and the resource-dependence theory. The study will involve interviews and surveys among five entrepreneurs. The research aims to start a deeper look into the reasons behind the engagement of individuals and entrepreneurs in CSR projects.